Improving Student Learning Outcomes Through Problem Based Learning Models in Indonesian Language Subjects for Elementary School Students - Arsad Arsad; Muhammad Yusnan (AIQU: Journal Multidiscipliner of Science, 2023)
This research aims to improve student learning outcomes through the Problem Based Learning (PBL) learning model in Indonesian language learning in Class V of Wameo 2 State Elementary School. This type of research is classroom action research, each cycle consisting of 4 stages, namely planning, action, observation and reflection. The research subjects chosen were 16 students in class V of Wameo State Elementary School 2, even semester of the 2021/2022 academic year, consisting of 10 male students and 6 female students. The data collection techniques used were observation, test sheets, interviews and documentation. Based on the research results in cycle I and cycle II, results were obtained which showed an increase in learning outcomes, namely from the test results in cycle I there were 10 students who completed (62.50%) and 6 students (37.50%). Incomplete with an average score of 65. .62. Student learning outcomes in cycle II were 14 students (87.50%) completed and 2 students (12.50%) incomplete with an average score of 92.5. The results of this research indicate that the use of the Problem Based Learning learning model can improve student learning outcomes from cycle I to cycle II.